Zero SAPs and ash free antiwear additives: Schiff bases of salicylaldehyde with 1,2-phenylenediamine, 1,4-phenylenediamine, and 4,4′-diaminodiphenylenemethane and their synergistic interactions with borate ester - Rastogi R.B.; Maurya J.L.; Jaiswal V. (My University, 2025)
Schiff bases of salicylaldehyde with 1,2-phenylenediamine (H2Saloph), 1,4-phenylenediamine (H2Salpph), and 4,4′- diaminodiphenylmethane (H2Saldphm) have been synthesized for their application as ecofriendly, zero sulfated ash, phosphorous, and sulfur (SAPs) and ash-free antiwear additives. Testing of the compounds was carried out in paraffin oil on a four-ball testing machine using steel balls and zinc dibutyl dithiophosphate (ZDDP) as a reference additive. Their synergistic behavior with borate ester was also studied. Testing of the compounds (1% w/v) was performed at various loads for 30- min test duration and for different times at 392 N load. On the basis of various tribological parameters, the following order is given for the activity of the compounds: H2Saldphm > H2Salpph > H2Saloph When the mixtures of Schiff bases and borate ester were tested, they showed a high amount of synergy. Schiff bases follow the above order in their mixtures, too. The efficiencies of the synergistic formulations were far better than that of the standard ZDDP. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to study the topography of the wear scar. In the presence of synthesized additives, a tribofilm was formed on the rubbing surface, reducing its roughness. Energydispersive X-ray (EDX) analysis showed chemisorption of the additive resulting in the formation of a tribofilm that bore the load. The surface roughness was diminished appreciably when borate ester was added to the additives, which may be due to the formation of a wear-resistant tribofilm. © Society of Tribologists and Lubrication Engineers.